THE EFFECT OF CHARISMATIC LEADERSHIP, ORGANIZATIONAL COMMUNICATION AND JOB SATISFACTION ON EMPLOYEE PERFORMANCE (CASE STUDY AT THE AL-QUR’AN WAQF BOARD, HEAD OFFICE JAKARTA) - Liana Fitria; Herminingsih Anik (Dinasti International Journal of Education Management And Social Science, 2021)
Research entitled "The Effect of Charismatic Leadership, Organizational Communication and Job Satisfaction on Employee Performance (Case Study on the Al-Quran Waqf Board at the Jakarta Head Office)" mission to know the influence of Charismatic Leadership, Organizational Communication and Job Satisfaction. on Employee Performance. This study's subjects were 61 employees who work at the Al-Qur'an Waqf Board at the Jakarta Head Office. The data obtained were analyzed using multiple linear regression with the help of the SPSS program version 23. Results show a positive and significant influence on the Organizational Communication Variables and Job Satisfaction Variables on the Performance of Employees who work at the Al-Qur'an Waqf Board at the Jakarta Head Office. However, there is an insignificant influence on the performance of the Al-Qur'an Waqf Board employees at the Jakarta Head Office. It is recommended that companies communicate vertically, especially downward communication, so that superiors communicate more frequently with subordinates and the company can set strategies in the form of a wage scale so that no employee feels disadvantaged, either new employees or old employees.